Aluminum alloy forgings

By adjusting the content range of elements in aluminum alloy forging materials and optimizing heat treatment and forging processes, the problem of excessive Fe content affecting material performance is solved, and high strength, ductility and corrosion resistance of aluminum alloy forging materials are achieved, reducing carbon emissions.

JP7654882B1Active Publication Date: 2025-04-01KOBE STEEL LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2024174169
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2024-01-15
Filing Date
2024-10-03
Publication Date
2025-04-01
Estimated Expiration
2044-10-03

AI Technical Summary

Technical Problem

When manufacturing high-strength, high-ductility and corrosion-resistant aluminum alloy forged materials, the Fe content exceeds 0.4% will affect the strength, ductility and corrosion resistance of the material, and the production of new aluminum ingots requires a large amount of electricity, resulting in an increase in carbon emissions.

Method used

By adjusting the content range of elements such as Si, Fe, Cu, Mg, Ti and Zn in aluminum alloy forging materials, and optimizing through heat treatment and forging processes, the particle growth of Fe is suppressed, the microstructure of the material is maintained, and the high strength, ductility and corrosion resistance of the material are ensured.

Benefits of technology

With the Fe content exceeding 0.4%, the high strength, ductility and corrosion resistance of aluminum alloy forged materials have been achieved, reducing dependence on new aluminum ingots and reducing carbon emissions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007654882000005
    Figure 0007654882000005
  • Figure 0007654882000001
    Figure 0007654882000001
  • Figure 0007654882000002
    Figure 0007654882000002
Patent Text Reader

Abstract

Provided is an aluminum alloy forging material that is excellent in strength, ductility, fatigue properties, and corrosion resistance despite containing more than 0.4 mass % Fe. [Solution] An aluminum alloy forging material containing Si: 0.7% or more and 1.5% or less by mass, Fe: more than 0.4% by mass and 0.67% or less by mass, Cu: more than 0.4% by mass and 0.8% or less by mass, Mg: 0.85% or more and 1.3% or less by mass, Ti: 0.005% or more and 0.07% or less by mass, Zn: 0.25% or less by mass, and at least one selected from the group consisting of Mn: 0.1% or more and 0.95% or less by mass, Cr: more than 0.1% by mass and 0.4% or less by mass, and Zr: 0.05% or more and 0.3% or less by mass, with the remainder being unavoidable impurities and Al, and having a crystallized particle area ratio of 3.2% or less and an average crystallized particle size of 8 μm or less.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an aluminum alloy forging used for automobile suspension parts and the like. [Background technology]

[0002] Aluminum alloy forgings used for automobile suspension parts such as upper arms and lower arms are required to have high strength, high ductility, high toughness, high corrosion resistance, fracture toughness, fatigue properties, etc., and various types have been developed to meet these requirements.

[0003] For example, Patent Document 1 describes an automobile suspension part made of an aluminum alloy forging material containing 0.5 to 1.25 mass% Mg, 0.4 to 1.4 mass% Si, 0.01 to 0.7 mass% Cu, 0.05 to 0.4 mass% Fe, 0.001 to 1.0 mass% Mn, 0.01 to 0.35 mass% Cr, 0.005 to 0.1 mass% Ti, and Zr is restricted to less than 0.15 mass%, with the remainder being Al and unavoidable impurities, in which the average area ratio of the crystallized precipitate density observed in the structure of the cross-sectional portion where the maximum stress occurs in the width direction cross-sectional structure at the maximum stress occurrence portion is 1.5% or less, and the average spacing between each grain boundary precipitate observed in the structure of the cross-sectional portion including a parting line generated during forging is 0.7 μm or more.

[0004] According to the invention described in Patent Document 1, it is described that even forged automobile suspension parts having a lightweight shape can have high strength, toughness, and corrosion resistance, but the Fe content is limited to 0.40 mass% or less.

[0005] On the other hand, Patent Document 2 states that it is possible to increase the blending ratio of recycled metal from city scraps and to use new metal with a low purity, and restricts the contents to Si: 0.4% by mass or more and 1.5% by mass or less, Fe: more than 0.4% by mass and 1.0% by mass or less, Cu: 0.40% by mass or less, Mg: 0.8% by mass or more and 1.3% by mass or less, Ti: 0.01% by mass or more and 0.1% by mass or less, Zn: 0.05% by mass or less, and Mn: 0.01% by mass or more and 1.0% by mass or less. The present invention describes an aluminum alloy forging material that contains at least one selected from the group consisting of Al: 0.0% by mass or less, Cr: 0.1% by mass or more and 0.4% by mass or less, and Zr: 0.05% by mass or more and 0.2% by mass or less, with the amount of hydrogen restricted to 0.25 ml / 100 g Al or less, the balance consisting of unavoidable impurities and Al, with an average crystal grain size of 50 μm or less, a crystallized particle area ratio of 3% or less, and an average crystallized particle size of 8 μm or less.

[0006] According to the invention described in Patent Document 2, it is described that an aluminum alloy forging material can be produced that has fracture toughness and fatigue properties equivalent to those of an aluminum alloy forging material containing 0.4 mass % or less of Fe. However, since the Cu amount is limited to 0.40 mass % or less, the strength is somewhat inferior. In addition, in light of the current situation of resource depletion, recycling of various items is progressing, and recycling of metals, which are consumed in large quantities, has also been carried out for some time. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] JP 2008-163445 A [Patent Document 2] JP 2011-214093 A Summary of the Invention [Problem to be solved by the invention]

[0008] High-strength, high-ductility, and high-corrosion-resistant aluminum alloy forgings are usually produced from primary aluminum ingots produced by refining bauxite. However, refining bauxite requires a huge amount of electricity, which is supplied by thermal power plants. For this reason, there is a problem in that a large amount of CO2 is emitted when producing high-strength, high-ductility, and high-corrosion-resistant aluminum alloy forgings using primary aluminum ingots.

[0009] However, it is known that if the amount of virgin aluminum ingots used is reduced and the amount of recycled ingots used increases, the amount of impurities such as Fe contained in the molten aluminum increases, causing intermetallic compounds to crystallize during casting, which adversely affects the strength, ductility, corrosion resistance, etc. of the aluminum alloy forgings manufactured using these raw materials. Therefore, there was an issue in that in order to limit the amount of Fe, virgin aluminum ingots manufactured by emitting large amounts of CO2 had to be used.

[0010] The present invention has been made in consideration of the above-mentioned problems, and aims to provide an aluminum alloy forging material that has the same strength, ductility, fatigue properties and corrosion resistance as aluminum alloy forging materials having an Fe content of 0.4 mass% or less, even when the Fe content exceeds 0.4 mass%. [Means for solving the problem]

[0011] In order to solve the above-mentioned problems, the inventors conducted extensive research into the chemical composition of aluminum alloy forgings. As a result, they discovered that by controlling the contents of various added elements, such as Fe, which affects tensile properties (strength, ductility (elongation)), fatigue properties, corrosion resistance, and microstructure, Ti, which is usually added to refine the cast structure, and Cu, which affects strength and corrosion resistance, within specified ranges, it is possible to obtain aluminum alloy forgings that are excellent in strength, ductility, fatigue properties, and corrosion resistance, despite containing more than 0.4 mass% Fe, and thus created the present invention.

[0012] That is, the present invention relates to the following. [1] Si: 0.7% by mass or more and 1.5% by mass or less, Fe: more than 0.4 mass% and not more than 0.67 mass% Cu: more than 0.4 mass% and not more than 0.8 mass% Mg: 0.85% by mass or more and 1.3% by mass or less, Ti: 0.005% by mass or more and 0.07% by mass or less, Zn: 0.25% by mass or less, At least one selected from the group consisting of Mn: 0.1% by mass or more and 0.95% by mass or less, Cr: more than 0.1% by mass and 0.4% by mass or less, and Zr: 0.05% by mass or more and 0.3% by mass or less, The balance is unavoidable impurities and Al, An aluminum alloy forging material having a crystallite area ratio of 3.2% or less and an average crystallite size of 8 μm or less. [2] The aluminum alloy forging according to [1], wherein the length of a high-angle grain boundary having a tilt angle of 15° or more is 4.15 mm or more, as measured in an area of ​​150 μm × 150 μm by a SEM-EBSD method at the center of wall thickness in a cross section perpendicular to the metal flow direction of the aluminum alloy forging. [3] The aluminum alloy forging according to [1] or [2], having a 0.2% yield strength of 345 MPa or more and an elongation of 12.5% ​​or more. Effect of the Invention

[0013] According to the present invention, it is possible to provide an aluminum alloy forging material that is excellent in strength, ductility, fatigue properties, and corrosion resistance despite containing more than 0.4 mass % Fe. [Brief description of the drawings]

[0014] [Figure 1] FIG. 1 is a plot of the relationship between the Fe content and elongation in the aluminum alloy forgings of the examples and comparative examples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] [Aluminum alloy forgings] The aluminum alloy forging according to the present invention has the following features: Si: 0.7% by mass or more and 1.5% by mass or less, Fe: more than 0.4 mass% and not more than 0.67 mass% Cu: more than 0.4 mass% and not more than 0.8 mass% Mg: 0.85% by mass or more and 1.3% by mass or less, Ti: 0.005% by mass or more and 0.07% by mass or less, Zn: 0.25% by mass or less, At least one selected from the group consisting of Mn: 0.1% by mass or more and 0.95% by mass or less, Cr: more than 0.1% by mass and 0.4% by mass or less, and Zr: 0.05% by mass or more and 0.3% by mass or less, The balance is composed of unavoidable impurities and Al, This is an aluminum alloy forging material having a crystallized particle area ratio of 3.2% or less and an average crystallized particle size of 8 μm or less. Each of the constituent elements of the aluminum alloy forging material according to the present invention will be described below.

[0016] (Si: 0.7 mass% or more and 1.5 mass% or less) Silicon is an essential element that contributes to high strength (proof stress). If the silicon content is too low, the crystal grains become coarse, and sufficient strength (tensile strength and 0.2% proof stress) cannot be obtained by artificial aging treatment. On the other hand, if the silicon content is too high, the corrosion resistance is reduced. Furthermore, the workability is also hindered, such as by reducing the elongation. Therefore, the silicon content is set to 0.7% by mass or more and 1.5% by mass or less, preferably 0.8% by mass or more and 1.3% by mass or less, and more preferably 0.9% by mass or more and 1.1% by mass or less.

[0017] (Fe: more than 0.4 mass% and less than 0.67 mass%) Fe, together with Mn and Cr, forms dispersed particles (dispersed phase) to hinder grain boundary migration after recrystallization, and has the effect of preventing the crystal grains from becoming coarse and refining the crystal grains. Here, in the case of conventional aluminum alloy forgings with an Fe content of 0.4 mass % or less, when the material is heat-treated at high temperatures, the dispersed particles also dissolve in solid solution, and the crystal grains tend to become coarse due to recrystallization. When Fe is contained in an amount of more than 0.4 mass% as in the present invention, the density of the dispersed particles increases, so that recrystallization can be suppressed even when heated at a high temperature. In addition, by performing a forging process, the Fe-based crystallized particles can be refined and rounded. Furthermore, by refining the crystal grains, the progress of fatigue cracks can be suppressed, and fatigue properties can be improved.

[0018] If the Fe content is too low, these effects are not obtained. On the other hand, if the Fe content is too high, the precipitates such as Al-Fe-Si intermetallic compounds become coarse. The coarse precipitates deteriorate the elongation, fatigue properties, corrosion resistance, and the like. The present inventors investigated the relationship between the Fe content and elongation, and created a regression equation (FIG. 1). It was found that sufficient elongation can be obtained if the Fe content is 0.67 mass% or less. Details will be described in the Examples section. Therefore, the Fe content is more than 0.4 mass% and 0.67 mass% or less. It is preferably more than 0.40 mass% and 0.65 mass% or less, and more preferably more than 0.40 mass% and 0.55 mass% or less.

[0019] (Cu: more than 0.4 mass% and less than 0.8 mass%) Cu not only contributes to improving strength through solid solution strengthening, but also has the effect of significantly accelerating the age hardening of the final product during aging treatment. If the Cu content is too low, these effects are lost. On the other hand, if the Cu content is too high, the susceptibility of the metal structure of the aluminum alloy forging material to stress corrosion cracking and intergranular corrosion is significantly increased, and the corrosion resistance and durability of the aluminum alloy forging material are reduced. Therefore, the Cu content is set to more than 0.4 mass% and not more than 0.8 mass%, more preferably more than 0.4 mass% and not more than 0.5 mass%.

[0020] (Mg: 0.85 mass% or more and 1.3 mass% or less) Mg is an essential element that contributes to high strength (proof stress). If the Mg content is too low, the amount of age hardening during artificial aging treatment decreases. Also, crystal grains are likely to become coarse. Furthermore, corrosion resistance also decreases. On the other hand, if the Mg content is too high, the strength (proof stress) becomes too high, inhibiting forgeability. Also, corrosion resistance and the like decrease. Therefore, the Mg content is set to 0.85% by mass or more and 1.3% by mass or less, preferably 1.0% by mass or more and 1.2% by mass or less.

[0021] (Ti: 0.005 mass% or more and 0.07 mass% or less) Ti has the effect of refining the crystal grains of the ingot. If the Ti content is too low, this effect is not achieved. In addition, the crystal grains become coarse and the strength decreases. On the other hand, if the Ti content exceeds 0.07 mass%, the crystal grains of the forged material after heat treatment tend to become coarse, which reduces the fatigue properties. The coarse crystal particles become the starting point of fracture and reduce the elongation. Therefore, the Ti content is set to 0.005 mass% or more and 0.07 mass% or less, preferably 0.01 mass% or more and 0.06 mass% or less.

[0022] (Zn: 0.25% by mass or less) Zn, which is easily mixed in as an impurity, is preferably 0% by mass, and if the content exceeds 0.25% by mass, the strength, elongation, and corrosion resistance decrease. Therefore, the Zn content is set to 0.25% by mass or less, preferably 0.05% by mass or less.

[0023] (Containing at least one selected from the group consisting of Mn: 0.1 mass% or more and 0.95 mass% or less, Cr: more than 0.1 mass% and 0.4 mass% or less, and Zr: 0.05 mass% or more and 0.3 mass% or less) Of these, Mn and Cr form dispersed particles (dispersed phases) made of Al-Mn and Al-Cr intermetallic compounds in which Fe, Mn, Cr, Si, Al, etc. are selectively bonded according to their contents during homogenization heat treatment and the subsequent hot forging.

[0024] Although it depends on the manufacturing conditions, the dispersed particles of Mn and Cr have the effect of preventing grain boundary migration after recrystallization, thereby preventing the crystal grains from becoming coarse.

[0025] If the content of Mn and Cr is too small, these effects cannot be expected, and the grains become coarse, resulting in a decrease in strength. On the other hand, excessive content of these elements causes a decrease in elongation. For this reason, it is preferable to contain at least one of Mn and Cr, and the content of Mn is 0.1 mass% or more and 0.95 mass% or less, preferably 0.2 mass% or more and 0.6 mass% or less, and the content of Cr is more than 0.1 mass% and 0.4 mass% or less, preferably more than 0.1 mass% and 0.3 mass% or less, more preferably more than 0.1 mass% and 0.2 mass% or less.

[0026] Zr generates dispersed particles (dispersed phase) like Mn and Cr. In the case of Zr, depending on the casting conditions, such as when Ti is included, it may hinder the refinement of the crystal grains of the ingot and cause the crystal grains to become coarse. It may also cause the fatigue properties to deteriorate. Therefore, it is desirable to add Zr in a range that does not cause the crystal grains to become coarse during casting. Specifically, the content of Zr is 0.05% by mass or more and 0.3% by mass or less, preferably 0.05% by mass or more and 0.1% by mass or less.

[0027] The aluminum alloy forging material according to the present invention can obtain the necessary strength for, for example, automobile suspension parts that require high strength by containing Si, Cu, and Mg in the above ranges, can refine the cast structure by containing Ti in the above ranges, and can suppress recrystallization during solution treatment and form fine crystals by containing Mn, Cr, and Zr in the above ranges. Therefore, high strength can be ensured. And, in the present invention, even when Fe is contained in such a large amount, by carrying out forging, Fe-containing crystallized particles are reduced, refined, and rounded, and the crystal grains are refined, thereby ensuring elongation, fatigue properties, and corrosion resistance.

[0028] (balance: unavoidable impurities and Al) The balance is made up of inevitable impurities and Al. Examples of inevitable impurities include C, Ni, Na, Ca, V, and Hf. These are easily mixed in as impurities and impair the properties of automobile suspension parts, so it is preferable not to include them, but it is acceptable if they are each 0.05% by mass or less and the total amount is 0.10% by mass or less.

[0029] In addition, B is also an impurity, but like Ti, it has the effect of refining the crystal grains of the ingot and improving the workability during extrusion and forging. However, if it is contained in an amount exceeding 300 ppm, it also forms coarse crystal precipitates, which reduces the above-mentioned workability. Therefore, the B content is preferably 300 ppm or less.

[0030] <Crystallized matter> The aluminum alloy forged material of the present invention has a crystallite area ratio of 3.2% or less and an average crystallite size of 8 μm or less.

[0031] (Crystallized area ratio: 3.2% or less) The crystallized area ratio is determined by the amount of the added element and the amount of solid solution thereof. By making the crystallized area ratio 3.2% or less, it is possible to suppress the decrease in elongation caused by the increase in the number of crack propagation paths. In addition, it is possible to suppress the decrease in corrosion resistance caused by the mother phase around the crystallized particles being easily corroded. The crystallized area ratio is more preferably 3.1% or less, and even more preferably 3.0% or less.

[0032] The crystallized area ratio can be calculated by taking a backscattered electron image of a cross section perpendicular to the metal flow of the forged material at the center of the wall thickness using a SEM and analyzing the image. A specific calculation method will be shown in the Examples section.

[0033] (Average crystal size: 8μm or less) The average size of the crystallites is determined by the amount of the added element, the solidification rate, etc. By making the average size of the crystallites 8 μm or less, it is possible to prevent the crystallites from becoming the starting point of cracks in a tensile test and reducing the elongation. The average size of the crystallites is more preferably 7 μm or less, and even more preferably 6 μm or less.

[0034] The average size of crystallites can be determined by taking a backscattered electron image of a cross section perpendicular to the metal flow of the forged material at the center of the wall thickness using an SEM, and then converting it into a circle of the same area using analysis software to calculate the average size.

[0035] (Average grain size: 50μm or less) The average crystal grain size affects mechanical properties. From the viewpoint of tensile properties and fatigue properties, the average crystal grain size is preferably 45 μm or less, and more preferably 40 μm or less.

[0036] The average grain size can be calculated by the short-axis intercept method, which involves etching the center of the wall thickness of a cross section perpendicular to the metal flow direction of a forged material, photographing it with an optical microscope, drawing a straight line perpendicular to the long axis of the grains, counting the number of grains on the line, and dividing the distance of the line by the number of grains.

[0037] (Length of high angle grain boundary: 4.15mm or more) In the aluminum alloy forging according to the embodiment of the present invention, it is preferable that the length of a high-angle grain boundary having a tilt angle of 15° or more is 4.15 mm or more, as measured by SEM-EBSD in an area of ​​150 μm × 150 μm at the center of the wall thickness in a cross section perpendicular to the metal flow direction of the aluminum alloy forging. The high angle grain boundary length affects mechanical properties. From the viewpoint of tensile properties and fatigue properties, the high angle grain boundary length is more preferably 4.2 mm or more, and further preferably 4.3 mm or more.

[0038] (Low angle grain boundary length: 2.0mm or more) The length of the minor grain boundary affects the mechanical properties. From the viewpoint of tensile properties and fatigue properties, the length of the minor grain boundary is preferably 2.0 mm or more, more preferably 2.2 mm or more, and further preferably 2.5 mm or more.

[0039] The SEM-EBSD (EBSP) method is a crystal orientation analysis method that uses an SEM equipped with an Electron Back Scattering (Scattered) Diffraction Pattern (EBSD) system. The length of high-angle grain boundaries and low-angle grain boundaries can be calculated automatically by performing crystal orientation analysis with SEM-EBSD method in an area of ​​150μm×150μm at the center of the thickness of the cross section perpendicular to the metal flow of the forged material in 0.5μm observation steps, defining the boundary where the orientation difference between adjacent crystal grains is 15° or more as high-angle grain boundaries and the boundary where the orientation difference is 5° to 15° as low-angle grain boundaries, and analyzing the data using analysis software (TSL OIM Analysis 7 ×64). Note that data with a CI value (Confidence Index) of 0.1 or less is excluded from the analysis.

[0040] <Tensile properties> (0.2% yield strength: 345MPa or more) The 0.2% proof stress of the aluminum alloy forging of the present invention is preferably 345 MPa or more. If it is less than 345 MPa, the strength required for the forging of an automobile suspension part may not be ensured. The 0.2% proof stress is more preferably 355 MPa or more, and further preferably 360 MPa or more.

[0041] (Growth: over 12.5%) The elongation (%) of the aluminum alloy forging of the present invention is preferably more than 12.5%. If it is less than 12.5%, the formability may be insufficient for use as a forging material for automobile suspension parts. The elongation is preferably 13% or more, more preferably 13.5% or more.

[0042] (Tensile strength: 370MPa or more) From the viewpoint of strength as a forging material for automobile suspension parts, the tensile strength of the aluminum alloy forging of the present invention is preferably 370 MPa or more, more preferably 380 MPa or more, and further preferably 385 MPa or more.

[0043] The tensile properties and fatigue properties of the aluminum alloy forgings can be adjusted by using the above-mentioned chemical composition and the manufacturing method described below.

[0044] The elongation, 0.2% yield strength, and tensile strength of aluminum alloy forgings can be measured by a metal material tensile test in accordance with JIS Z 2241 (revised in 2011). Specifically, a tensile test piece (No. 4 test piece) in accordance with JIS Z 2201 is cut out from the center of a cross section at any point so that the axis of the test piece is parallel to the metal flow of the forging, and a tensile test is performed at room temperature (25°C). The number of samples for mechanical property measurement is 2, and each is calculated as an average value. In this way, the elongation, 0.2% yield strength, and tensile strength can be calculated.

[0045] <Fatigue properties> (Number of repeated cycles at 170 MPa in fatigue tests using unnotched rotating bending fatigue test pieces: 1×10 6 cycles or more) The number of repeated cycles to fracture of the aluminum alloy forging of the present invention at a repeated stress of 170 MPa in a fatigue test using an unnotched rotating bending fatigue test piece is 1×10 6 In a fatigue test using a rotating bending fatigue test piece without a notch, the number of repeated cycles to fracture at a repeated stress of 170 MPa is preferably 2×10 6 cycles or more, preferably 3 x 10 6 More than a cycle.

[0046] (Number of repeated stresses at 70 MPa in fatigue tests using notched rotating bending fatigue test pieces: 1×10 6 cycles or more) In a fatigue test using a notched rotating bending fatigue test piece of the aluminum alloy forging of the present invention, the number of repeated cycles to fracture under a repeated stress of 70 MPa was 1×10 6 In a fatigue test using a rotating bending fatigue test piece with a notch, the number of repeated cycles to fracture at a repeated stress of 70 MPa is preferably 2×10 6 cycles or more, preferably 3 x 10 6 More than a cycle.

[0047] The fatigue properties of aluminum alloy forgings can be measured by a rotating bending fatigue test of metal materials in accordance with JIS Z 2274. Specifically, for rotating bending fatigue test pieces without notches, rotating bending fatigue test pieces (No. 2 test pieces) in accordance with JIS Z 2274 are cut out from any point parallel to the metal flow of the aluminum alloy forgings, and a rotating bending fatigue test is performed at a repeated stress of 170 MPa. For rotating bending fatigue test pieces with notches, annular semicircular grooved test pieces (groove corner R, ρ, is 0.31 mm) in accordance with JIS Z 2274 are cut out from any point parallel to the metal flow of the aluminum alloy forgings, and a rotating bending fatigue test is performed at a repeated stress of 70 MPa. The N number for fatigue property measurement is set to 2, and the minimum value is calculated. In this manner, the fatigue properties can be calculated.

[0048] The fatigue properties of the aluminum alloy forgings can be adjusted by using the above-mentioned chemical composition and the manufacturing method described below.

[0049] The aluminum alloy forgings according to the present invention described above can have strength, elongation, fatigue properties and corrosion resistance equivalent to those of aluminum alloy forgings containing 0.4 mass % or less Fe. That is, the aluminum alloy forging material according to the present invention can contain more than 0.4 mass% Fe, which has a detrimental effect on strength, elongation, etc. Therefore, the amount of virgin aluminum metal used during production of the aluminum alloy forging material can be reduced, and CO2 emissions can be significantly reduced.

[0050] [Manufacturing method of aluminum alloy forgings] Next, a method for producing an aluminum alloy forging according to the present invention will be described. The manufacturing method of the aluminum alloy forging of the present invention is not particularly limited, but the above-mentioned aluminum alloy forging can be suitably manufactured by a manufacturing method including a casting step, a homogenization heat treatment step, a heating step, a forging step, a solution treatment step, a quenching step, and an artificial aging treatment step in this order. The manufacturing method of the aluminum alloy forging material may further include a step that does not impair the desired effect of the present invention, such as an extrusion step performed between the homogenization heat treatment step and the heating step, or a forging roll step performed between the heating step and the forging step.

[0051] (Casting process) The casting process is a process for casting an ingot of an aluminum alloy having the above-mentioned composition. The composition has already been described in detail, so a detailed description thereof will be omitted. The casting step is preferably carried out at a heating temperature of 710 to 810° C. and a cooling rate to the liquidus temperature of 7° C. / sec or more. If the heating temperature in the casting process is 710℃ or higher, the melting time can be shortened and the work can be done efficiently. Also, if the heating temperature in the casting process is 810℃ or lower, the generation of dross, which is an oxide, is suppressed and metal loss is reduced, allowing the ingot to be obtained efficiently. If the cooling rate to the liquidus temperature is less than 7° C. / sec, the crystallized particles become coarse, making it impossible to achieve a crystallized particle area ratio of 3.2% or less. The heating temperature is preferably 710 to 750° C., and the cooling rate to the liquidus temperature is preferably 10° C. / sec or faster.

[0052] Casting can be carried out by melting casting methods such as continuous casting, semi-continuous casting, and hot top casting, among which continuous casting is preferred.

[0053] (Homogenization heat treatment process) The next homogenization heat treatment step is a step of homogenizing the ingot cast in the casting step at 420 to 560°C for 2.5 to 8 hours. By setting the heating temperature in the homogenization heat treatment step to 420°C or higher and the heating time to 2.5 hours or longer, the crystallized particles are sufficiently dissolved and the area ratio of the crystallized particles is reduced, so that the elongation of the product can be ensured. On the other hand, by setting the heating temperature in the homogenization heat treatment step to 560°C or lower and the heating time to 8 hours or shorter, the coarsening of the dispersed particles is suppressed, so that the dispersed particles can be uniformly, finely, and densely dispersed. In other words, the effect of refining the crystal grains is easily obtained, and the average crystal grain size is reduced. The heating temperature in the homogenization heat treatment step is preferably 500 to 540° C., and the heating time is preferably 4 to 8 hours.

[0054] (Heating process) The next heating step is a step of heating the ingot that has been homogenized in the homogenization heat treatment step at 400 to 545° C. for 0.5 hours or more. As described above, Fe, together with Mn and Cr, has the effect of preventing grain boundary migration after recrystallization by generating dispersed particles (dispersed phase). Therefore, by adding a large amount of Fe, even if a sufficient heating process is performed, the number and density of dispersed particles can be made to be the same as that of the conventional material, and coarsening of the crystal grains can be prevented, so that the crystal grains can be maintained fine. Therefore, the tensile properties can be maintained to the same level as that of the conventional material. This effect can be realized by sufficiently heating the ingot in this heating process before the forging process, dissolving the Fe-based crystallized matter, reducing it, and further refining it.

[0055] If the heating temperature in the heating step is 440°C or higher and the heating time is 0.5 hours or longer, even in the case of an aluminum alloy forging material containing a large amount of Fe as in the present invention, the Fe-based crystallized substances are dissolved in solid solution, and the elongation can be maintained at the same level as that of the conventional material. On the other hand, if the heating temperature is 545°C or lower, the occurrence of eutectic melting due to heat generated during processing is suppressed, so that voids are unlikely to occur and mechanical properties are unlikely to deteriorate. In addition, the dispersed particles are unlikely to become coarse and have a low density due to heat treatment, and the effect of crystal grain refinement is easily obtained. The heating temperature in the heating step is preferably 440 to 545°C.

[0056] (Forging process) The next forging process is a process in which the ingot heated in the heating process is forged at a forging end temperature of 350°C or higher and a reduction ratio of 50 to 95% to obtain a forged material of a predetermined shape. The reduction ratio is defined as (1-(L1 / L0)) x 100, where L0 is the height of the material before forging and L1 is the height after forging. If the forging end temperature in the forging process is 350°C or higher, residual strain is not large, so recrystallization is unlikely to occur and the crystal grains are unlikely to become coarse. In addition, if the reduction rate in the forging process is 50% or more, casting defects can be compressed, and further, crystal grains and crystallized substances can be made sufficiently small. If the reduction rate is 95% or less, the processing rate is not too high, and coarsening of crystal grains due to recrystallization is unlikely to occur. In addition, it is preferable that the forging end temperature is as high as possible within the range that does not exceed the heating temperature. The forging end temperature is preferably 370° C. or higher, and the rolling reduction is preferably 70 to 90%.

[0057] Forging under such conditions can be carried out, for example, by a mechanical press or a hydraulic press.

[0058] (Solution treatment process) The next solution treatment step is a step of subjecting the forged material obtained in the forging step to solution treatment at 480 to 580°C for more than 0 hours and up to 24 hours. This solution treatment can promote the solid solution of additive elements that provide strength in the artificial aging treatment step described below, and can increase elongation by refining crystallized particles. When the heating temperature in the solution treatment step is 480°C or higher and the heating time is longer than 0 hours, the solution treatment is sufficient, and good elongation and strength (tensile strength and 0.2% yield strength) can be obtained. On the other hand, when the heating temperature in the solution treatment step is 580°C or lower and the heating time is 24 hours or shorter, the crystal grains are less likely to coarsen, the average crystal grain size is less likely to increase, and good strength (tensile strength and 0.2% yield strength) can be obtained. The heating temperature in the solution treatment step is preferably 540 to 560° C., and the heating time is preferably 2.5 to 8.0 hours.

[0059] (Quenching process) The next step is the quenching step, in which the forged material that has been solution-treated in the solution treatment step is quenched at 75° C. or lower. By quenching, the strength can be improved. If the quenching temperature in the quenching step is 75° C. or less, sufficient quenching is achieved, and the strength can be sufficiently improved in the artificial aging treatment step described below. The lower limit of the quenching temperature may be approximately the normal temperature of the water used for quenching, that is, 20±15° C. (5 to 35° C.) as specified by JIS Z 8703.

[0060] (Artificial aging process) The next step, the artificial aging treatment step, is a step in which the forged material quenched in the quenching step is artificially aged at 160 to 250°C for 0.5 to 20 hours. The treatment from the solution treatment step to this artificial aging treatment step is so-called artificial aging hardening treatment. By this artificial aging treatment, for example, the strength required for automobile suspension parts can be obtained. If the heating temperature in the artificial aging treatment step is 160°C or higher and the heating time is 0.5 hours or longer, sufficient strength, fatigue properties, and corrosion resistance can be obtained. On the other hand, if the heating temperature in the artificial aging treatment step is 250°C or higher and the heating time is 20 hours or longer, excessive overaging occurs, and sufficient strength and elongation cannot be obtained. The heating temperature in the artificial aging treatment step is preferably 170 to 250° C., and the heating time is preferably 3 to 12 hours.

[0061] According to the manufacturing method of the aluminum alloy forgings described above, it is possible to manufacture an aluminum alloy forging having an Fe content exceeding 0.4 mass % but having the same strength, elongation, fatigue properties and corrosion resistance as an aluminum alloy forging having an Fe content of 0.4 mass % or less. EXAMPLES

[0062] The present invention will be specifically described below with reference to examples of the present invention, although the technical scope of the present invention is not limited thereto.

[0063] (Production of forging materials) The aluminum alloy forgings according to Nos. 1 to 6 were produced using aluminum alloys having the chemical compositions shown in Table 1 under the following conditions. First, the molten aluminum alloy was gravity cast into a metal mold to produce an ingot. The casting conditions were a heating temperature of 720°C and a cooling rate to the liquidus temperature of 10 to 15°C / sec. Each ingot was face-machined to a diameter of 55 mm and length of 100 mm, and then homogenized under the conditions shown in Table 2 below, heated, hot die forged using a hydraulic press, solution treated, quenched, and artificial aging treated to produce the aluminum alloy forgings with the respective numbers.

[0064] [Table 1]

[0065] [Table 2]

[0066] [Table 3]

[0067] The tensile properties, fatigue properties, average grain size (μm), high angle grain boundary length (mm), low angle grain boundary length (mm), crystallized area ratio (%), average crystallized size (μm), corrosion rate (mm / y) as general corrosion resistance, and stress corrosion cracking resistance (SCC resistance) of the forged materials No. 1 to 6 were evaluated. The tensile properties were tensile strength (MPa), 0.2% proof stress (MPa), and elongation (%). The fatigue properties were measured by the number of repeated cycles to fracture at a repeated stress of 170 MPa in a fatigue test using a rotating bending fatigue test piece without a notch, and the number of repeated cycles to fracture at a repeated stress of 70 MPa in a fatigue test using a rotating bending fatigue test piece with a notch. These evaluations were carried out as follows.

[0068] <Tensile properties> Tensile properties were measured using a tensile tester according to JIS Z 2201 (No. 4 test piece) by cutting out from any point of the aluminum alloy forging material so as to be parallel to the metal flow direction, and using a tensile tester according to JIS Z 2241. Regarding the tensile properties, a 0.2% yield strength of 345 MPa or more was deemed pass, and less than 345 MPa was deemed fail, while an elongation of more than 12.5% ​​was deemed pass, and 12.5% ​​or less was deemed fail.

[0069] <Fatigue properties> For the fatigue properties, rotating bending fatigue test specimens without notches were prepared by cutting out rotating bending fatigue test specimens (No. 2 test specimens) conforming to JIS Z 2274 from any point parallel to the metal flow of the aluminum alloy forging, and evaluated at a repeated stress of 170 MPa. For the rotating bending fatigue test specimens with notches, test specimens with annular semicircular grooves conforming to JIS Z 2274 (groove corner R, ρ, is 0.31 mm) were prepared by cutting out from any point parallel to the metal flow of the aluminum alloy forging, and evaluated at a repeated stress of 70 MPa. The number of repeated cycles to fracture at a repeated stress of 170 MPa in fatigue tests using rotating bending fatigue test pieces without notches, and the number of repeated cycles to fracture at a repeated stress of 70 MPa in fatigue tests using rotating bending fatigue test pieces with notches, were both 1×106 cycles or more was considered a pass.

[0070] In addition, Fig. 1 is a plot diagram of the relationship between the Fe content and elongation in the aluminum alloy forgings No. 1 to 6. From this, a regression equation was created. It can be seen that if the Fe content is 0.67 mass% or less, the elongation exceeds 12.5%, and sufficient elongation can be obtained.

[0071] (Average grain size) The average grain size (μm) was calculated by etching the center of the thickness of a cross section perpendicular to the metal flow direction of the aluminum alloy forging, photographing it with an optical microscope at 400x, drawing a straight line perpendicular to the long axis of the grains, counting the number of grains on the line, and dividing the distance of the line by the number of grains measured. If the average crystal grain size exceeds 50 μm, the tensile properties and fatigue properties deteriorate, so an average crystal grain size of 50 μm or less is considered to be acceptable, and one exceeding 50 μm is considered to be unacceptable.

[0072] (Length of high angle grain boundary) The SEM-EBSD (EBSP) method is a crystal orientation analysis method that uses an SEM equipped with an Electron Back Scattering (Scattered) Diffraction Pattern (EBSD) system. The length of high-angle grain boundaries was calculated automatically by analyzing the crystal orientation using SEM-EBSD method in an area of ​​150μm×150μm at the center of the thickness of the cross section perpendicular to the metal flow of the forged material, with an observation step of 0.5μm, and the boundaries where the orientation difference between adjacent crystal grains is 15° or more were defined as high-angle grain boundaries. Data with a CI value (Confidence Index) of 0.1 or less was excluded from the analysis.

[0073] The length of high-angle grain boundaries is measured in an area of ​​150 μm × 150 μm by the SEM-EBSD method in the metal structure of the center of the thickness of aluminum alloy forgings. When the length of high-angle grain boundaries with an inclination angle of 15° or more is less than 4.15 mm, fatigue properties decrease, and the number of repeated fractures at a repeated stress of 170 MPa in fatigue tests using unnotched rotating bending fatigue test pieces and at a repeated stress of 70 MPa in fatigue tests using notched rotating bending fatigue test pieces is 1 × 10 6 Therefore, the length of high-angle grain boundaries with an inclination angle of 15° or more, measured by SEM-EBSD in an area of ​​150 μm × 150 μm at the center of the wall thickness of a cross section perpendicular to the metal flow of the aluminum alloy forging, was determined to pass if the length was 4.15 mm or more.

[0074] (Low angle grain boundary length) The SEM-EBSD (EBSP) method is a crystal orientation analysis method that uses an SEM equipped with an Electron Back Scattering (Scattered) Diffraction Pattern (EBSD) system. The length of the low-angle grain boundary was calculated automatically by analyzing the crystal orientation using SEM-EBSD method in an area of ​​150μm×150μm at the center of the thickness of the cross section perpendicular to the metal flow of the forged material, with an observation step of 0.5μm, and the boundary where the orientation difference between adjacent crystal grains is 5° to 15° was defined as a low-angle grain boundary. The length of the low-angle grain boundary was calculated automatically by analyzing the data using analysis software (TSL OIM Analysis 7 ×64). Note that data with a CI value (Confidence Index) of 0.1 or less was excluded from the analysis.

[0075] The length of low-angle grain boundaries is measured in a range of 150 μm × 150 μm by the SEM-EBSD method in the metal structure of the center of the thickness of aluminum alloy forgings. When the length of low-angle grain boundaries with an inclination angle of 5° to 15° is less than 2.0 mm, the fatigue properties decrease, and the number of repeated fractures at a repeated stress of 170 MPa in fatigue tests using unnotched rotating bending fatigue test pieces and at a repeated stress of 70 MPa in fatigue tests using notched rotating bending fatigue test pieces is 1×106 Therefore, the length of low-angle grain boundaries, measured in an area of ​​150 μm × 150 μm by SEM-EBSD method at the center of the thickness of a cross section perpendicular to the metal flow direction of the aluminum alloy forging, was determined to pass if the length of the low-angle grain boundaries with an inclination angle of 5° to 15° was 2.0 mm or more.

[0076] <Crystallized matter> (Crystallized area ratio) The crystallized area ratio (%) was calculated by taking a 400x backscattered electron image using a SEM (JEOL, JSM-IT700HR) at the center of the wall thickness in a cross section perpendicular to the metal flow of the forged material, calculating the area of ​​white contrast using image analysis (WinROOF2018, Ver.4.7.0), and dividing the area by the total area where image analysis was performed. If the crystallized matter area ratio exceeds 3.2%, the elongation decreases and it becomes impossible to ensure elongation of more than 12.5%, so a crystallized matter area ratio of 3.2% or less is considered to be acceptable, and one exceeding 3.2% is considered to be unacceptable.

[0077] (Average crystal size) The average crystallite size (μm) was determined by taking a 400x backscattered electron image using a SEM (JEOL, JSM-IT700HR) at the center of the wall thickness in a cross section perpendicular to the metal flow of the forged material, and converting it into a circle of the same area using analysis software to calculate the average size. If the average crystallite size exceeds 8 μm, the elongation decreases and it becomes impossible to secure elongation of more than 12.5%, so an average crystallite size of 8 μm or less is considered to be acceptable, and one exceeding 8 μm is considered to be unacceptable.

[0078] <General corrosion resistance> (corrosion rate) The corrosion rate (mm / y) was measured by preparing a flat plate from an aluminum alloy forging and subjecting it to the alternate immersion method of ASTM G47. Here, the corrosion rate (mm / y) represents the amount of corrosion (mm) in one year (365 days). The test conditions consisted of repeatedly immersing the plate in salt water and then pulling it out for 30 days, measuring the weight before and after the test, and calculating the corrosion rate using the following formula (1). Here, M is the corrosion weight loss (g / 30 days), ρ is the density 2.7 (g / cm 3), S is the area of ​​the evaluation section (cm 2 ) is shown.

[0079]

number

[0080] If the corrosion rate exceeds 0.12mm / y, the aluminum alloy forging material will not be able to function satisfactorily as an automobile suspension part. Therefore, a corrosion rate of 0.12mm / y or less is considered to be acceptable, and one exceeding 0.12mm / y is considered to be unacceptable.

[0081] <Stress corrosion cracking resistance> The stress corrosion cracking resistance (SCC resistance) was evaluated according to the provisions of JIS H 8711 by preparing C-ring shaped test pieces from aluminum alloy forgings and subjecting them to an alternating immersion method. The SCC test was carried out under the conditions of a load stress of 180 MPa (tensile) and a period of 30 days, assuming use as an automobile suspension part. After the test, the test pieces were observed to see whether stress corrosion cracking had occurred. The stress corrosion cracking resistance was evaluated as passed when no stress corrosion cracking was observed in the test piece by visual inspection, and failed when stress corrosion cracking was observed in the test piece.

[0082] Table 1 shows the tensile properties of the forged materials No. 1 to 6, the number of cycles to fracture at a repeated stress of 170 MPa in a fatigue test using an unnotched rotating bending fatigue test piece, the number of cycles to fracture at a repeated stress of 70 MPa in a fatigue test using a notched rotating bending fatigue test piece, the average crystal grain size (μm), the high-angle grain boundary length (mm), the low-angle grain boundary length (mm), the crystallized particle area ratio (%), the average crystallized particle size (μm), and the corrosion rate (mm / y) and SCC resistance as general corrosion resistance.

[0083] As shown in Table 1, the aluminum alloy forging material No. 4 satisfied all of the requirements of the present invention, and thus obtained favorable evaluation results. On the other hand, the forged materials No. 1 and No. 2 have an Fe content below the lower limit. Forged material No. 3 had a small high-angle grain boundary length because the Ti content exceeded the upper limit, resulting in failure in the number of repeated fractures at a repeated stress of 170 MPa in a fatigue test using a rotating bending fatigue test piece without a notch, and failure in the number of repeated fractures at a repeated stress of 70 MPa in a fatigue test using a rotating bending fatigue test piece with a notch. In the forged materials No. 5 and No. 6, the Fe content exceeded the upper limit, so the Al-Fe-Si crystals became coarse and the crystal area ratio became large. As a result, the elongation and corrosion rate were unacceptable.

Claims

1. Si: 0.7% by mass or more and 1.5% by mass or less, Fe: more than 0.4 mass% and not more than 0.67 mass%; Cu: more than 0.4 mass% and not more than 0.8 mass%; Mg: 0.85% by mass or more and 1.3% by mass or less, Ti: 0.005% by mass or more and 0.07% by mass or less, Zn: 0.25 mass% or less, Contains at least one selected from the group consisting of Mn: 0.1 mass% or more and 0.95 mass% or less, Cr: more than 0.1 mass% and 0.4 mass% or less, and Zr: 0.05 mass% or more and 0.3 mass% or less, The balance is composed of unavoidable impurities and Al, An aluminum alloy forging having a crystallized particle area ratio of 3.2% or less and an average crystallized particle size of 8 μm or less.

2. 2. The aluminum alloy forging according to claim 1, wherein a length of a high-angle grain boundary having a tilt angle of 15° or more is 4.15 mm or more as measured in an area of ​​150 μm × 150 μm by a SEM-EBSD method at a thickness center portion of a cross section perpendicular to a metal flow direction of the aluminum alloy forging.

3. The aluminum alloy forging material according to claim 1 or 2, having a 0.2% yield strength of 345 MPa or more and an elongation of more than 12.5%.

Citation Information

Patent Citations

  • Aluminum alloy cast member for forging

    JP1994256880A

  • Automobile chassis parts and its manufacturing method

    JP2008163445A

  • HIGH STRENGTH Al ALLOY FORGED MATERIAL HAVING EXCELLENT CORROSION RESISTANCE AND WORKABILITY AND METHOD FOR PRODUCING THE SAME

    JP2011106011A

  • Aluminum alloy forging and method for manufacturing same

    JP2011214093A

  • Aluminum alloy material

    JP2013221161A